Sport-specific and anthropometric factors of quality in junior male water polo players - Idrizovic, K.; Uljevic, O.; Ban, D.; Spasic, M.; Rausavljevic, N. (Collegium Antropologicum, 2013)
There is evident lack of studies which examined anthropological determinants of success in water polo. The aim of this investigation was to study the physical fitness differences between two qualitative levels of junior water polo players (males; 16-18 years of age; 6+ year of experience in water polo). The sample (N=54) comprised of 13 members of the junior national-squad (5 centres and 8 perimeter players), and 41 team-athletes (11 centres and 30 perimeter players). The sample of variables included: four anthropometric measures (body height, body mass, BMI and body fat percentage), and five sport-specific fitness tests (20-meters-sprint-swimming, maximal dynamometric force in eggbeater kick, in-water vertical jump, drive-shoot-speed, and sport-swimming-endurance). Discriminant analysis and t-test revealed no significant differences between national-squad and team-players for centre players. The national-squad perimeters were advanced over their team-level peers in most of the fitness capacities and body-height. The result highlights the necessity of the playing-position-specific approach in defining anthropological factors of success in team-sports.